2009
DOI: 10.22260/isarc2009/0013
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Autonomous Loading of Bulk Material

Abstract: Autonomous loading implies a fully automated scenario in which automated excavating machines, such as front-loaders, load themselves from a heap of bulk material and deliver to the dumping site. The process comprises all the functions of loading, navigating, obstacle detection and avoidance and unloading to be automated and controlled by a supervisory computer. Autonomous loading benefits a number of industries such as construction and mining, from economical view point as well as other concerns like operators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Automation of a manipulator under constant and forceful contact with an uncertain environment has proved, however, to be a challenging control problem. Autonomous excavation is one of the oldest applications in field robotics (see the reviews [1]- [3]) yet, despite almost three decades of research, no commercial deployment of a fully autonomous excavator has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Automation of a manipulator under constant and forceful contact with an uncertain environment has proved, however, to be a challenging control problem. Autonomous excavation is one of the oldest applications in field robotics (see the reviews [1]- [3]) yet, despite almost three decades of research, no commercial deployment of a fully autonomous excavator has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…where the joint velocity vector for the wheel, boom link and bucket isq = [φ w ,φ l ,φ b ] T and the joint angles are defined as in [2].…”
Section: Machine Modelmentioning
confidence: 99%
“…The system and loading operation models, described in Sec. 2 Dynamics [30] and run with the settings listed in…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The leading machine properties during operation are productivity, energy efficiency and operability [3]. There are three key technical challenges [4] about automatizing the LHD: (1) obtaining bulk material pile models, (2) planning optimal shoveling trajectory, and (3) developing a controller that responds quickly to rapidly changing external forces [5]. We focus on the second challenge.…”
Section: Introductionmentioning
confidence: 99%